Wireless Network Security Theories and Applications - Chen, Lei.; Ji, Jiahuang; Zhang, Zihong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Wireless Network Security Theories and Applications discusses the relevant security technologies, vulnerabilities, and potential threats, and introduces the corresponding security standards and protocols, as well as provides solutions to security concerns. Authors of each chapter in this book, mostly top researchers in relevant research fields in the U.S. and China, presented their research findings and results about the security of the following types of wireless networks: Wireless Cellular Networks, Wireless Local Area Networks (WLANs), Wireless Metropolitan Area Networks (WMANs), Bluetooth Networks and Communications, Vehicular Ad Hoc Networks (VANETs), Wireless Sensor Networks (WSNs), Wireless Mesh Networks (WMNs), and Radio Frequency Identification (RFID). The audience of this book may include professors, researchers, graduate students, and professionals in the areas of Wireless Networks, Network Security and Information Security, Information Privacy and Assurance, as well as Digital Forensics. Lei Chen is an Assistant Professor at Sam Houston State University, USA; Jiahuang Ji is an Associate Professor at Sam Houston State University, USA; Zihong Zhang is a Sr. software engineer at Jacobs Technology, USA under NASA contract.
Challenges in Wireless Network Security -- Security in Centralized Wireless Networks -- Security in Decentralized Wireless Networks.-Security in Hybrid Wireless Networks.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Telecommunication; Computer Science; Computer Communication Networks; Data Encryption; Communications Engineering, Networks